2023
DOI: 10.3390/molecules28145317
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Doxorubicin Embedded into Phospholipid Nanoparticles and Targeted Peptide-Modified Phospholipid Nanoparticles with DNA

Abstract: The interactions of dsDNA with new targeted drug delivery derivatives of doxorubicin (DOX), such as DOX embedded into phospholipid nanoparticles (NPhs) and DOX with the NGR targeted peptide-modified NPhs were studied electrochemically by differential pulse voltammetry technique. Screen-printed electrodes (SPEs), modified with stable fine dispersions of carbon nanotubes (CNTs), were used for quantitative electrochemical investigations of direct electrochemical oxidation of guanine, adenine, and thymine heterocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Earlier, we showed that electrochemical oxidation of dsDNA was successfully achieved on SPE/CNT after dsDNA immobilization by physical entrapment/absorption on the surface of the modified electrodes. Modification of SPEswith CNT stabilized with carboxymethylcellulose (SPE/CNT) allowed the registering of electrochemical oxidation of guanine, adenine and thymine in the immobilized dsDNA [ 40 , 41 , 71 ]. Adding nanosized titanium (IV) oxide TiO 2 improved the sensitivity of electrodes for the registration of dsDNA ( Figure 4 a,b), as in the case of protein registration [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier, we showed that electrochemical oxidation of dsDNA was successfully achieved on SPE/CNT after dsDNA immobilization by physical entrapment/absorption on the surface of the modified electrodes. Modification of SPEswith CNT stabilized with carboxymethylcellulose (SPE/CNT) allowed the registering of electrochemical oxidation of guanine, adenine and thymine in the immobilized dsDNA [ 40 , 41 , 71 ]. Adding nanosized titanium (IV) oxide TiO 2 improved the sensitivity of electrodes for the registration of dsDNA ( Figure 4 a,b), as in the case of protein registration [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on this observation, we used SPEs only for single measurements. This regimen is typical for the irreversible electrochemical process [ 40 , 41 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations